Pengembangan Sistem Informasi Fretboard Gitar Interaktif Berbasis Web Menggunakan React dan Laravel Untuk Visualisasi Tangga Nada - Romiz Aisy; Dewi Oktafiani (Sekolah Vokasi, Universitas Sebelas Maret, 2026)
Learning to play an instrument until mastering it is certainly not an easy task. Even after being able to play the instrument, there are still challenges in the form of music theory. Most people give up on learning music because they find it difficult to understand these concepts. In today’s era, learning music theory can be easily accessed through the internet, whether in the form of videos or text. However, most of the available music materials are still not sufficient to help learners truly understand, due to the lack of visualization of the theory as applied to the instrument they play. This system is designed using the Waterfall method and implemented with the Laravel framework and the React library. The guitar fretboard information system can help players gain insight into how music theory works within the guitar they are playing.